Heteroepitaxial growth of cadmium carbonate at dolomite and calcite surfaces: Mechanisms and rates. (15th May 2017) - Callagon, Erika Blanca R.; Lee, Sang Soo; Eng, Peter J.; Laanait, Nouamane; Sturchio, Neil C.; Nagy, Kathryn L.; Fenter, Paul
Abstract: The systematic variation of rates and the mechanism of cadmium uptake on the (1 0 4) surface of dolomite (CaMg(CO3 )2 ) were investigated using in situ and ex situ atomic force microscopy (AFM), ex situ specular X-ray reflectivity (XR), and ex situ X-ray fluorescence (XRF). Selected experiments were performed on the calcite (CaCO3 ) (1 0 4) surface for comparison. Aqueous solutions of CdCl2, CaCl2, and NaHCO3, undersaturated with respect to calcite and supersaturated with respect to otavite (CdCO3 ) and the (Cd x Ca1− x )CO3 solid solution, were reacted with dolomite surfaces for minutes to days. Calcite substrates were reacted with solutions containing 1–50 μM CdCl2, and with no added Ca or CO3 . Thin carbonate films following the Stranski–Krastanov growth mode were observed on both substrates. Specular XR and XRF revealed the formation of nm-thick Cd-rich carbonate films that were structurally ordered with respect to the dolomite (1 0 4) plane. Epitaxial films adopted the calcite crystal structure with a d 104 -spacing (3.00 Å) larger than those of pure dolomite (2.88 Å) and otavite (2.95 Å) indicating either a solid solution with x  ≈ 0.5, or a strained Cd-rich carbonate with a composition near that of otavite. The growth rate r of this phase increases with the initial supersaturation of the solution with respect to the solid solution, β max, and follows the empirical relationship, as determined from XRF measurements, given by: r = 10 - 4.88 ± 0.42 ( β max 2.29 ± 0.24 - 1 ), ( in units of atoms of Cd / Å 2 / h ) . The morphology of the overgrowth also varied with β max, as exemplified by AFM observations. Growth at step edges occurred over the entire β max range considered, and additional growth features including 3 Å high monolayer islands and ∼25 Å high tall islands were observed when log β max > 1 . On calcite, in situ XR indicated that this phase is similar to the Cd-rich overgrowth formed on dolomite and images obtained from X-ray reflection interface microscopy (XRIM) reveal the existence of laterally variable Cd-rich domains.